A Role for Tectal Midline Glia in the Unilateral Containment of Retinocollicular Axons - Wu, Da-Yu (J Neurosci, 1998)
Retinal fibers approach close to the tectal midline but do not encroach on the other side. Just before the entry of retinal axons into the superior colliculus (SC), a group of radial glia differentiates at the tectal midline; the spatiotemporal deployment of these cells points to their involvement in the unilateral containment of retinotectal axons. To test for such a barrier function of the tectal midline cells, we used two lesion paradigms for disrupting their radial processes in the neonatal hamster: (1) a heat lesion was used to destroy the superficial layers of the right SC, including the midline region, and (2) a horizontally oriented hooked wire was inserted from the lateral edge of the left SC toward the midline and was used to undercut the midline cells, leaving intact the retinorecipient layers in the right SC. In both cases, the left SC was denervated by removing its contralateral retinal input. Animals were killed 12 hr to 2 weeks later, after intraocular injections of anterograde tracers to label the axons from the remaining eye. Both lesions resulted in degeneration of the distal processes of the tectal raphe glia and in an abnormal crossing of the tectal midline by retinal axons, leading to an innervation of the opposite (“wrong”) tectum. The crossover occurred only where glial cell attachments were disrupted. These results document that during normal development, the integrity of the midline septum is critical in compartmentalizing retinal axons and in retaining the laterality of the retinotectal projection.